Instrumental delivery and ultrasound : a multicentre randomised controlled trial of ultrasound assessment of the fetal head position versus standard care as an approach to prevent morbidity at instrumental delivery. (11th April 2014) - Ramphul, M; Ooi, PV; Burke, G; Kennelly, MM; Said, SAT; Montgomery, AA; Murphy, DJ
<x xml:space="preserve">Abstract</x> Objective To determine whether the use of ultrasound can reduce the incidence of incorrect diagnosis of the fetal head position at instrumental delivery and subsequent morbidity. Design Two‐arm, parallel, randomised trial, conducted from June 2011 to December 2012. Setting Two maternity hospitals in the Republic of Ireland. Sample A cohort of 514 nulliparous women at term (≥37 weeks of gestation) with singleton cephalic pregnancies, aiming to deliver vaginally, were recruited prior to an induction of labour or in early labour. Methods If instrumental delivery was required, women who had provided written consent were randomised to receive clinical assessment (standard care) or ultrasound scan and clinical assessment (ultrasound). [Correction added on 17 April 2014, after first online publication: Sentence was amended.] Main outcome measure Incorrect diagnosis of the fetal head position. Results The incidence of incorrect diagnosis was significantly lower in the ultrasound group than the standard care group (4/257, 1.6%, versus 52/257, 20.2%; odds ratio 0.06; 95% confidence interval 0.02–0.19; P < 0.001). The decision to delivery interval was similar in both groups (ultrasound mean 13.8 minutes, SD 8.7 minutes, versus standard care mean 14.6 minutes, SD 10.1 minutes, P = 0.35). The incidence of maternal and neonatal complications, failed instrumental delivery, and caesarean section was not significantly different between the two groups. Conclusions An ultrasound assessment prior to instrumental delivery reduced the incidence of incorrect diagnosis of the fetal head position without delaying delivery, but did not prevent morbidity. A more integrated clinical skills‐based approach is likely to be required to prevent adverse outcomes at instrumental delivery.